(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The parametres of arterial blood pressure determined in standard conditions in three groups of patients while carrying out multicomponent endotracheal inhalation anaesthesia with halogen-containing volatile anesthetics have been analysed (halothane was used in the first group, isoflurane - in the second group, sevoflurane - in the third group). The control group was made by almost healthy people. Two subgroups depending on the ASA physical status were analyzed. The analysis took into account the systolic, diastolic and pulse arterial blood pressure. The authors offered to calculate coefficients of arterial blood pressure. The conclusion has been made that the integrative indicator of arterial blood pressure objectively reflects the quality of anesthetic protection at stages of anesthesia and can be used as a criterion of adequacy of anesthesia. It does not depend on age, estimation of the ASA physical status, and concrete halogen-containing volatile anesthetics.